Intra-Operative Mitomycin-C as Adjuvant Therapy in External and Endonasal Dacryocystorhinostomy: Systematic Review and Meta-Analysis - Sousa, Tamata T. S. [UNESP]; Schellini, Silvana A. [UNESP]; Meneghim, Roberta L. F. S. [UNESP]; Cataneo, Antonio J. M. [UNESP] (Springer, 2020)
Purpose To evaluate the effect of mitomycin-C (MMC) on the success of external (Ex-DCR) or endoscopic dacryocystorhinostomy (En-DCR). Method A systematic review of randomized clinical trials of Ex- or En-DCR with and without the use of MMC to treat primary acquired nasolacrimal duct obstruction (NLDO) was done. Two authors independently searched six databases from 1990 to 2019, using the terms dacryocystorhinostomy and mitomycin-C. Statistical and meta-analyses were performed using RevMan 5.3 software. Results Twenty-seven studies involving 2158 surgeries were included in this systematic review. The Ex-DCR group comprised 14 studies [odds ratio (OR): 2.74; 95% confidence intervals (CI) 1.54-4.87; I-2 = 30%], while the En-DCR group 13 studies (OR: 1.69; 95% CI 1.21-2.37; I-2 = 0%). The use of MMC slightly increased the success rate of Ex- or En-DCR (OR: 2.1; 95% CI 1.52-2.9; I-2 = 14%). Conclusion The intraoperative use of MMC is safe and slightly improves the success rate of Ex- or En-DCR. However, the evidence was very weak.
Keywords: Endoscopic dacryocystorhinostomy; External dacryocystorhinostomy; Meta-analysis; Mitomycin-C; Nasolacrimal duct obstruction; Success; Systematic review